Analysis of the Influence of Leadership Style, Intellectual Intelligence, and Organizational Culture of UPZ Baznas Sub-district on the Success of the BAZNAS Program in Banyuwangi Regency - Z Arif Armawan; Yuniorita Indah Handayani; Dedy Wijaya Kusuma (International Journal of Economics, Commerce, and Management, 2025)
The objectives of this study formulated in the formulation of the problem are as follows: (1) To analyze the influence of leadership style partially on the performance of administrators and fulltimers of UPZ Baznas sub-districts in Banyuwangi Regency; To analyze the influence of intellectual intelligence partially on the performance of administrators and fulltimers of UPZ Baznas sub-districts in Banyuwangi Regency; (3) To analyze the influence of organizational culture partially on the performance of administrators and fulltimers of UPZ Baznas sub-districts in Banyuwangi Regency; (4) To analyze the influence of leadership style, intellectual intelligence and organizational culture simultaneously on the performance of administrators and fulltimers of UPZ Baznas sub-districts in Banyuwangi Regency. This study uses the method used is to use a quantitative approach with a questionnaire data collection technique distributed to respondents. The data analysis technique uses multiple linear regression analysis techniques assisted by the SPSS program. The results of the study obtained include: (1) leadership style partially has a significant effect on the performance of administrators and fulltimers of UPZ Baznas sub-districts in Banyuwangi Regency; (2) intellectual intelligence partially has a significant effect on the performance of managers and full-timers of UPZ Baznas sub-districts in Banyuwangi Regency; (3) organizational culture partially has a significant effect on the performance of managers and full-timers of UPZ Baznas sub-districts in Banyuwangi Regency; (4) leadership style, intellectual intelligence and organizational culture have an effect on the performance of managers and full-timers of UPZ Baznas sub-districts in Banyuwangi Regency. A good leadership style, having high intellectual intelligence and a comfortable organizational culture can also improve performance.